2006
DOI: 10.1007/s00436-006-0211-2
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi: experimental parasitism of bone and cartilage

Abstract: Trypanosoma cruzi causes Chagas' disease, a systemic infection that affects cells of meso-, endo-, and ectodermic origin. However, as far as we know, the presence of T. cruzi stages in bone has not been reported previously, and it has scarcely been investigated in cartilage. We inoculated 7- and 20-day-old (8 and 15 g) NMRI albino mice i.p. with metacyclic trypomastigotes from Rhodnius prolixus used for xenodiagnosis of mice previously infected with mammalian, human, and triatomines isolates, characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…This lowlevel parasitemia is in agreement with previous findings at the acute timepoint used for analysis. While others have reported parasite distribution to lung, spleen and liver in cases when animals have been immunosuppressed (Calabrese et al, 1992) and even parasitism of bone and cartilage (Morocoima et al, 2006), it has become increasingly clear from a number of studies that the genetics of the parasite and host play a defining role in the tissue distribution of T. cruzi (Melo and Brener, 1978;Ben Younes-Chennoufi et al, 1988;McCabe et al, 1989;Andrade et al, 2002;Franco et al, 2003;Marinho et al, 2004). Although the pathogenesis of Chagas disease is multivariate, the persistence of T. cruzi has been suggested as playing a fundamental role in disease progression (Anez et al, 1999;Zhang and Tarleton, 1999;Tarleton, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lowlevel parasitemia is in agreement with previous findings at the acute timepoint used for analysis. While others have reported parasite distribution to lung, spleen and liver in cases when animals have been immunosuppressed (Calabrese et al, 1992) and even parasitism of bone and cartilage (Morocoima et al, 2006), it has become increasingly clear from a number of studies that the genetics of the parasite and host play a defining role in the tissue distribution of T. cruzi (Melo and Brener, 1978;Ben Younes-Chennoufi et al, 1988;McCabe et al, 1989;Andrade et al, 2002;Franco et al, 2003;Marinho et al, 2004). Although the pathogenesis of Chagas disease is multivariate, the persistence of T. cruzi has been suggested as playing a fundamental role in disease progression (Anez et al, 1999;Zhang and Tarleton, 1999;Tarleton, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These organs are often the focus of Chagas disease research, since these are the well-characterized disease manifestations. While other studies have identified trypanosomes in liver, spleen and lung tissue (Melo and Brener, 1978) and, more recently, bone and cartilage (Morocoima et al, 2006), these distributions generally follow the use of immunosuppressive therapy (Calabrese et al, 1992;Calabrese, 1999;Taniwaki et al, 2005) to facilitate robust parasite proliferation and expansion. Regardless of the mode of infection or treatment regimen, the sacrifice of animals has typically been required to obtain information on dissemination of parasites and detection of parasites in specific tissues following infection.…”
Section: Introductionmentioning
confidence: 99%
“…The epimastigote form replicates in the vector's gut, then differentiates to a highly motile form, the metacyclic trypomastigote, which invades mammalian host cells after transmission. Potentially any nucleated cell type may be parasitized in any tissue the trypomastigote can reach 4‐16 . After invasion and escape from a parasitophorous vacuole into the cytosol, another transition occurs to the amastigote form, which replicates repeatedly and then differentiates to generate a population of pleomorphic tissue/bloodstream form trypomastigotes.…”
Section: Trypanosoma Cruzi: a Formidable Foementioning
confidence: 99%
“…Sites reported to harbour the highest acute infection intensities include skeletal, smooth and cardiac muscle, mononuclear phagocytes and adipose tissues. Conversely, T. cruzi is comparatively rare where the blood/oxygen supply is poor, for example in osteocytes and chondrocytes [42], cartilage [41] and in immune-privileged sites including ovaries and testes [43]. It is worth making a distinction between cell and tissue types, which is possible with microscopic detection of parasites, but not with methods that analyse homogenized tissue samples or macro-scale imaging.…”
Section: Acute Infection and Tropismsmentioning
confidence: 99%